Physiology of spontaneous [Ca(2+)]i oscillations in the isolated vasopressin and oxytocin neurones of the rat supraoptic nucleus - Kortus, Stepan; Srinivasan, Chinnapaiyan; Forostyak, Oksana; Ueta, Yoichi; Sykova, Eva; Chvatal, Alexandr; Zapotocky, Martin; Verkhratsky, Alexei; Dayanithi, Govindan (Cell calcium, 2016)
The magnocellular vasopressin (AVP) and oxytocin (OT) neurones exhibit specific electrophysiological behaviour, synthesise AVP and OT peptides and secrete them into the neurohypophysial system in response to various physiological stimulations. The activity of these neurones is regulated by the very same peptides released either somato-dendritically or when applied to supraoptic nucleus (SON) preparations in vitro. The AVP and OT, secreted somato-dendritically (i.e. in the SON proper) act through specific autoreceptors, induce distinct Ca(2+) signals and regulate cellular events. Here, we demonstrate that about 70% of freshly isolated individual SON neurones from the adult non-transgenic or transgenic rats bearing AVP (AVP-eGFP) or OT (OT-mRFP1) markers, produce distinct spontaneous [Ca(2+)]i oscillations. In the neurones identified (through specific fluorescence), about 80% of AVP neurones and about 60% of OT neurones exhibited these oscillations. Exposure to AVP triggered [Ca(2+)]i oscillations in silent AVP neurones, or modified the oscillatory pattern in spontaneously active cells. Hyper- and hypo-osmotic stimuli (325 or 275 mOsmol/l) respectively intensified or inhibited spontaneous [Ca(2+)]i dynamics. In rats dehydrated for 3 or 5days almost 90% of neurones displayed spontaneous [Ca(2+)]i oscillations. More than 80% of OT-mRFP1 neurones from 3 to 6-day-lactating rats were oscillatory vs. about 44% (OT-mRFP1 neurones) in virgins. Together, these results unveil for the first time that both AVP and OT neurones maintain, via Ca(2+) signals, their remarkable intrinsic in vivo physiological properties in an isolated condition.
Keywords: vápníková signalizace; Animals; Spationtemporal dynamics; Green Fluorescent Proteins; Fluorescence spectrofluorimetry; Rats, Wistar; nucleus supraopticus; Hyper-osmolarity; Osmolar Concentration; neurony; Transgenic rats; Electrical activity; vasopresiny; Vasopressins; vápník; oxytocin; Osmoregulation; zelené fluorescenční proteiny; Supraoptic Nucleus; Neurons; Oxytocin; dehydratace; osmolární koncentrace; Calcium; Male; Ca(2+) oscillations; Hypothalamus; Calcium Signaling; Monomeric red fluorescence protein; Fura-2; Enhanced green fluorescence protein; Skewness; Hypo-osmolarity; Dehydration; zvířata; mužské pohlaví; Supraoptic nucleus; Lactation; Vasopressin; Magnocellular neurosecretory cells; potkani Wistar